Teaching sport concepts and skills : a tactical games approach - Mitchell, Stephen A., 1959-; Oslin, Judith L., 1950-; Griffin, Linda L., 1954- (Champaign, IL : Human Kinetics, 2021)
"This book is a blend of theory and practical application of the tactical games approach (also described as teaching games for understanding). Focusing on tactical awareness helps students develop problem-solving skills through game play. The tactical approach also allows teachers to individualize instruction for novice, developing, and advanced performers by either reducing or increasing the challenge of the tasks involved. Part I contains a thorough review of tactical games teaching and builds a sound conceptual understanding of the approach. Part II describes how elementary physical education teachers can use a conceptual approach to games teaching. Part III contains sport-specific chapters, including soccer, basketball, lacrosse, rugby, flag football, volleyball, badminton, tennis, softball, cricket, golf, and bowling"--
Includes bibliographical references
Keywords: Sports -- Study and teaching; Coaching (Athletics); Kent State University faculty publications